Economic Inequality Analysis Between Coastal Regions in Bengkulu Province 2018-2022 - Ifebri, Rihan; Wibowo, Hariz Eko; Khairani, Lathifah; Netta Agusti, Netta; Fauzi, Ariffatchur (AGRITROPICA : Journal of Agricultural Sciences, 2024)
Bengkulu Province in Sumatra exhibits lower economic growth than the average national level. Over the past five years, its average economic growth rate has been 4.82%, significantly below the national average of 5.31%. Economic disparities are evident between cities and regencies within the province, with coastal areas dominating yet showing significant variations in economic growth. This research used secondary data from the Bengkulu Provincial Statistics Agency for 2018-2022. It applies Klassen typology analysis and the Williamson Index to measure regional development disparities. The Klassen typology categorises Bengkulu City as an advanced and rapidly growing area, while Muko-Muko Regency and North Bengkulu Regency are identified as rapidly developing regions. Conversely, Kaur Regency and Seluma Regency are categorized as relatively underdeveloped areas. The Williamson Index analysis reveals significant disparities among the regencies/cities, with an average index of 0.385, indicating an increasing trend over the years. These disparities are influenced by regional characteristics and natural resource differences, hindering equitable development. These findings are expected to serve as a reference for the government in formulating appropriate policy strategies to reduce disparities and enhance economic growth in Bengkulu Province. Strategies such as job diversification and increased employment opportunities in the fisheries and processing industries can help address the disparities and poverty in coastal areas.